Arduino-Based Experiments: Leveraging Engineering Design and Scientific Inquiry in STEM Lessons - Dat, Nguyen Duc; Bien, Nguyen Van; Khuyen, Nguyen Thi To; Ha, Nguyen Thi Viet; An, Hoang Thi Thai; Anh, Ngo Thi Phuong (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
Organizing STEM activities based on scientific inquiry and engineering design processes is recommended for competency-based education in many countries, including Vietnam, to develop vital 21st-century practices. However, one of the challenges in the scientific inquiry process is the lack of equipment for conducting experiments. Therefore, there is a need for cost-effective and flexible instrument initiatives that students and teachers can design, create, and operate on their own. Additionally, real-world contexts like designing experiments for studying are also essential to engage students in engineering design processes. With its open-source platform, user-friendly interface, and limitless creative potential, Arduino is a valuable tool for STEM education. Hence, this study aims to develop Arduino-based experiments and suitable lesson plans to facilitate the implementation of STEM lessons following scientific inquiry and engineering design processes. In this study, we have proposed three Arduino-based experiments, followed by instruction plans, that students can build through engineering design processes to study several Physics concepts. The results show that microcontroller systems combined with common sensors are a low-cost yet effective approach with acceptable accuracy, allowing students to quantitatively and professionally investigate the relationship between physical quantities. In addition, 21st-century practices such as STEM literacy and design thinking are also concentrated in the context of working with the solutions for STEM problems.